Cooperative Enterprises for Disabled as Subjects of the Social Economy in Bulgaria – Overturned Realities - Stoyanova, Maria (Research Papers, 2016)
In the paper it is diagnosed the condition of cooperative enterprises for disabled in Bulgaria, as subjects of the social economy by results of empirical study implemented in 2013-2014. An analysis of the capabilities of these social enterprises for social inclusion and reintegration of people with disabilities is attempted. On the basis of representative empirical data the paradoxes or overturned realities in these cooperatives are revealed, namely: they have 60 years of history – but for more than 20 years have been completely forgotten by the state and society; they have facilities – but are not used as intended; they are social oasis for employment for people with disabilities – but there is no reproduction of the staff, they are unattractive for young professionals, because of the low earnings and low prestige in the society; they employ member cooperatives, real owners of capital – but they have no self-esteem and self-confidence to manage and decide the fate of cooperatives, including to develop social entrepreneurship; in recent post-crisis years, the social economy in developed countries shows sustainable development in a time of crisis – here, its structural elements, including and CED and social entrepreneurship are ignored by the state and society, etc. It is proposed possible solutions and concrete recommendations to the government on the micro, meso and macro level for overcoming of these and other paradoxes.
Keywords: Social economy; Cooperative enterprises; Cooperative enterprises for disabled; Production profile of cooperative enterprises for disabled; Overturned realities; Cooperatives